PENGINTEGRASIAN AJARAN TRI NGA MELALUI PEMBELAJARAN SBDP SUB SENI MUSIK SEBAGAI PENANAMAN KARAKTER BUDAYA BAIK DI SDN 2 WALUYO - Ulfa Diana, Anissa; Susanto, Rusnoto; Wahyu Astuti, Avinda; Septiyani, Lina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Ki Hadjar Dewantara's thoughts on education have become a distinctive image for the history of education in Indonesia. Ki Hadjar Dewantara's educational concept displays the uniqueness of Indonesian culture. One of Ki Hadjar's teaching methods is Tri Nga (understand, feel and act). Furthermore, Ki Hadjar Dewantara said, what is called "budipekerti" or character or in foreign languages ​​is called "character", namely "the completeness of the human soul" as a soul that is "based on spiritual law". People who have moral intelligence always think and feel and always use certain and constant measurements, scales and basics. Recognizing the character of the students we care for is an important aspect of the quality of human resources, because the quality of national character determines the progress of a nation. Character education can be integrated through all subjects, including SBdP learning, the music sub-material. Art lessons are an educational medium to shape students' good cultural character through artistic activities. This research aims to determine the integration of the Tri Nga teaching method (Ngerti,Ngroso,Nglakoni) in learning the art of music to instill good character at SDN 2 Waluyo. This research uses a qualitative approach. The data collection techniques used were observation, interviews and documentation. Data analysis techniques through data reduction, data presentation, drawing conclusions. The results of this research show that integrating Tri Nga teachings in learning the art of music can improve the education of good cultural character.